The effectiveness of age on HbA1c as a criterion for the diagnosis of diabetes in Chinese different age subjects. (12th June 2014) - Yang, Liyong; Shen, Ximei; Yan, Sunjie; Xu, Feipeng; Wu, Peiwen
Summary Objective To analyse the effectiveness of age on HbA1c as a criterion for the diagnosis of diabetes in Chinese different age subjects. Methods This retrospective study enrolled a total of 1147 outpatients with untreated newly diagnosed diabetes (aged 18–80 years, 42·55% women) from the Fujian Province, China, and 427 age and gender‐matched (control) subjects without diabetes. Receiver operating characteristic curve (ROC) was plotted to determine the performance of HbA1c against results of oral glucose tolerance test (OGTT) performed at the same time according to specific age groups. The ORs and 95%CIs between diabetes and other metabolic disorders were analysed. Results (i) HbA1c provided an age‐specific diagnosis for diabetes: there was a high diagnostic titter of HbA1c in the 18‐ to 39‐year age group; conversely, there was a low diagnostic titter of HbA1c in the ≥70‐year‐old age groups. (ii) After adjusted for age, individuals with diabetes by OGTT criteria but not by WHO HbA1c criteria had an increased chance of having abnormal weight, hypertriglyceridaemia, HDL hypocholesterolaemia and insulin resistance. (iii) The diagnostic cut‐off points of HbA1c for diabetes in different age groups (18–39, 40–49, 50–59, 60–69 and ≥70 years) were 6·1, 6·3, 6·4, 6·5 and 6·4, respectively. The age‐specific HbA1c criteria exhibited the higher positive rate, sensitivity and lower false‐negative rate when compared with WHO HbA1c criteria. Conclusions This provided evidence indicating that there may be drawbacks in the use of HbA1c in the diagnosis of diabetes. Thus, we proposed that the impact of introducing HbA1c for diabetes diagnosis should be considered in terms of age. Cohort studies are needed to further confirm the suitability of age‐specific HbA1c criteria for the diagnosis of diabetes.